A Family of NAI2-Interacting Proteins in the Biogenesis of the ER Body and Related Structures. Issue 1 (15th February 2019) - Wang, Zhe; Li, Xifeng; Liu, Nana; Peng, Qi; Wang, Yuexia; Fan, Baofang; Zhu, Cheng; Chen, Zhixiang
Abstract : Three related NAI2-interacting proteins from Arabidopsis are critical components in the biogenesis of ER bodies found only in the Brassicales and related structures likely also present in other plants. Abstract: Plants produce different types of endoplasmic reticulum (ER)-derived vesicles that accumulate and transport proteins, lipids, and metabolites. In the Brassicales, a distinct ER-derived structure called the ER body is found throughout the epidermis of cotyledons, hypocotyls, and roots. NAI2 is a key factor for ER body formation in Arabidopsis ( Arabidopsis thaliana ). Homologs of NAI2 are found only in the Brassicales and therefore may have evolved specifically to enable ER body formation. Here, we report that three related Arabidopsis NAI2-interacting proteins (NAIP1, NAIP2, and NAIP3) play a critical role in the biogenesis of ER bodies and related structures. Analysis using GFP fusions revealed that all three NAIPs are components of the ER bodies found in the cotyledons, hypocotyls, and roots. Genetic analysis with naip mutants indicates that they have a critical and redundant role in ER body formation. NAIP2 and NAIP3 are also components of other vesicular structures likely derived from the ER that are formed independent of NAI2 and are present not only in the cotyledons, hypocotyls, and roots, but also in the rosettes. Thus, while NAIP1 is a specialized ER body component, NAIP2 and NAIP3 are components of different types of ER-derived structures. Analysis of chimeric NAIP proteins revealed that their N-terminal domains play a major role in the functional specialization between NAIP1 and NAIP3. Unlike NAI2, NAIPs have homologs in all plants; therefore, NAIP-containing ER structures, from which the ER bodies in the Brassicales may have evolved, are likely to be present widely in plants.